(untitled) (European Journal of Pure and Applied Mathematics, 2021)
A set S âŠ† V (G) is a hop dominating set of G if for each v âˆˆ V (G) S, there existsÂ w âˆˆ S such that dG(v, w) = 2. It is a global hop dominating set of G if it is a hop dominatingset of both G and the complementÂ of G. The minimum cardinality of a global hop dominatingset of G, denoted by Î³gh(G), is called the global hop domination number of G. In this paper, we study the concept of global hop domination in graphs resulting from some binary operations. Â